Composite reinforced PVC pipe and preparation method thereof
By introducing modified carbon fiber and modified nanopolymium aluminum aluminum in PVC pipes, improve the compatibility and binding force of the material and PVC matrix, solve the limitations of traditional PVC pipes in high strength and durability, significantly improved its mechanical performance And thermal stability.
Patent Information
- Application Number
- CN202411552216.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-01-28
AI Technical Summary
Traditional PVC pipes have limitations in their performance in terms of high strength, impact resistance and temperature change resistance, which is difficult to meet a more demanding use environment. The bonding force between the reinforcement material and the PVC matrix is weak, resulting in interface layering or peeling, reducing the overall strength.
By introducing modified carbon fiber and modified nanopolymium, improve the compatibility and binding force of the material and the PVC matrix, and the dual screw extruder is used for melting and extrusion to prepare a composite PVC pipe.
It significantly improves the tensile strength, impact strength and durability of PVC pipes, improves mechanical properties and thermal stability, reduces the risk of interface sectors, and improves the stability and applicability of materials.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of PVC pipe production, and in particular to a composite reinforced PVC pipe and a preparation method thereof. Background Art
[0002] Polyvinyl chloride (PVC) is one of the five most common plastics, known for its early industrial production and wide application. Over the years, PVC has developed into the most widely used and consumed thermoplastic resin in the world. PVC is popular because it is cost-effective, easy to process, and has many excellent properties, such as good flame retardancy, electrical insulation, wear resistance and chemical corrosion resistance. These properties make PVC shine in many application areas, especially suitable for various needs in daily life. By adding different chemicals and adopting various formulations and production technologies, PVC products with different characteristics can be manufactured. Therefore, a wide variety of PVC products can be seen in life, from pipe fittings to sheets, to artificial leather, films and profiles. Due to its diverse forms and wide range of uses, PVC materials have played an important role in improving people's quality of life and provide many practical and convenient product options.
[0003] Compared with metal pipes, plastic pipes have lower energy consumption and cost, less impact on the environment, and are easier to install. Therefore, in the field of water and gas transportation, plastic pipes are gradually replacing traditional metal pipes. Among them, PVC (polyvinyl chloride) pipes, as an important category of plastic pipes, are widely used because of their advantages. PVC pipes are not only economical, but also show great flexibility and convenience during construction, becoming an indispensable part of modern piping systems.
[0004] However, traditional PVC pipes still have certain limitations in terms of high strength, impact resistance, and resistance to temperature changes, making it difficult to meet more demanding use environments. In order to improve the comprehensive performance of PVC pipes, composite reinforcement technology has gradually become a research hotspot. The interface compatibility of the reinforcement material directly affects the mechanical properties and service life of the pipe. The traditional reinforcement material has a weak bonding force with the PVC matrix, which easily leads to interface stratification or peeling, thereby reducing the overall strength of the PVC pipe. Summary of the invention
[0005] In view of this, the object of the present invention is to provide a composite reinforced PVC pipe and a preparation method thereof, which can overcome the problem of weak bonding between the reinforcing material and the PVC matrix and improve the strength of the PVC pipe.
[0006] The present invention solves the above technical problems by the following technical means: In a first aspect, the present invention provides a composite reinforced PVC pipe, wherein the raw materials for its preparation include, by weight: 110-130 parts of PVC resin, 10-15 parts of composite reinforcement material, 1-5 parts of stabilizer, 1-5 parts of titanium dioxide, 2-4 parts of plasticizer, 1-5 parts of lubricant, 0.5-2 parts of crosslinking agent, and 0.2-1.2 parts of dispersant; The composite reinforcement material comprises 6-10 parts of modified carbon fiber and 4-5 parts of modified nano-alumina. The modified carbon fiber is first oxidized and then modified with a coupling agent, and the modified nano-alumina is modified with aromatic alcohol and amino acid. Preferably, the stabilizer is a calcium-zinc composite stabilizer, the plasticizer is dioctyl phthalate, the lubricant is one or more of paraffin, polyethylene wax, and stearic acid amide, the crosslinking agent is dicumyl peroxide, and the dispersant is a mixture of polyvinyl alcohol and hydroxypropyl methylcellulose in a mass ratio of 1:2.
[0007] Preferably, the preparation steps of the modified carbon fiber include: A1. Soak the carbon fiber in the cleaning solvent for 0.5-1h, wash and dry; A2. Soak the dried carbon fiber in the oxidant solution for 0.5-2h, wash and dry; A3. Soak the dried carbon fiber in a coupling agent solution for 10-30 minutes, wash and dry to obtain the modified carbon fiber.
[0008] Preferably, the cleaning solvent in step A1 is one of acetone and ethanol, the oxidant solution in step A2 is one of chloric acid and nitric acid, and the coupling agent solution in step A3 is silane or titanate.
[0009] The oxidant solution can introduce polar functional groups such as carboxyl and hydroxyl groups on the surface of carbon fibers. These functional groups can improve the hydrophilicity of carbon fibers and their compatibility with matrix materials, laying the foundation for subsequent coupling reactions. By soaking the oxidized carbon fibers in the coupling agent solution, the coupling agent can react with the polar functional groups on the surface of the carbon fibers to form chemical bonds. This enhances the bonding between the carbon fibers and the PVC matrix material and improves the interface strength of the PVC pipe.
[0010] Preferably, the preparation steps of the modified nano-alumina include adding nano-alumina particles into an organic solvent, gradually adding aromatic amino acids under stirring, reacting at 100° C.-140° C. for 3-11 hours, washing and drying to obtain the modified nano-alumina.
[0011] Aromatic amino acid functional groups are introduced into the surface of nano-alumina, which increases its surface activity and hydrophilicity and improves its compatibility with the matrix material.
[0012] Preferably, the particle size of the nano-alumina is 10-100 nanometers.
[0013] Preferably, the mass ratio of the nano-alumina to the aromatic amino acid is 1:(0.5-1).
[0014] Preferably, the aromatic amino acids include tyrosine and phenylalanine.
[0015] In a second aspect, the present invention provides a method for preparing a composite reinforced PVC pipe, comprising the following steps: S1. Add the composite reinforcement material to half of the PVC resin, stir and mix, and stop stirring when the temperature rises to 160-190°C to obtain a first premix; S2. Stir and mix the other half of the PVC resin and the titanium dioxide and heat to 160-190°C and stop stirring to obtain a second premix; S3. The first premix and the second premix as well as the plasticizer, stabilizer, crosslinking agent, dispersant and lubricant are mixed, added into a twin-screw extruder, melt-extruded, cooled, shaped and cut to obtain the composite reinforced PVC pipe.
[0016] Preferably, the temperature of the twin-screw extruder is: 180°C-185°C in zone 1, 185°C-190°C in zone 2, 170°C-180°C in zone 3, 170°C-175°C in zone 4 and 165°C-170°C in zone 5.
[0017] Beneficial effects of the present invention: (1) Through oxidation treatment, the polar functional groups added to the surface of carbon fiber significantly improve its compatibility with water and other matrix materials, thereby enhancing the surface hydrophilicity. In addition, the introduction of coupling agent improves the interfacial bonding between carbon fiber and matrix and reduces the risk of interfacial delamination. As a result, the modified carbon fiber in PVC matrix can significantly improve the tensile strength, impact strength and durability of PVC pipes, and improve the mechanical properties of PVC pipes as a whole.
[0018] (2) The introduction of aromatic amino acid functional groups on the surface of nano-alumina significantly improves its surface activity and hydrophilicity, improves its compatibility with the matrix material, enhances the bonding force between nano-alumina and the PVC matrix, and reduces the risk of interface delamination. In addition, modified nano-alumina can significantly improve the tensile strength, impact strength and heat resistance of PVC pipes, and overall improve the mechanical properties and thermal stability of PVC pipes.
[0019] (3) The composite reinforced PVC pipe of the present invention significantly improves the tensile strength and impact strength by introducing modified carbon fiber and modified nano-alumina, while improving the thermal stability and interface bonding force, reducing the risk of interface delamination, and using environmentally friendly modified materials to improve safety and reduce the impact on the environment. DETAILED DESCRIPTION
[0020] The following will be combined with the specific embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention: Example 1
[0021] The composite reinforcement materials include 6kg of modified carbon fiber and 4kg of modified nano-alumina.
[0022] The preparation steps of modified carbon fiber are as follows: A1. Soak 6kg of carbon fiber in 10L of acetone for 0.5h, wash and dry; A2. Soak the dried carbon fiber in 12L nitric acid solution for 0.5h, wash and dry; A3. Soak the dried carbon fiber in 9L coupling agent solution for 10 minutes, wash and dry to obtain modified carbon fiber.
[0023] The preparation steps of modified nano-alumina are as follows: 6 kg of 10-nanometer nano-alumina particles were added to an organic solvent, and 3 kg of aromatic amino acid was gradually added under stirring. The mixture was reacted at 100° C. for 11 hours, and then washed and dried to obtain modified nano-alumina.
[0024] S1. Add 10kg of the composite reinforcement material to 55kg of PVC resin and stir and mix until the temperature rises to 160°C and then stop stirring to obtain a first premix; S2. 55kg of PVC resin and 1kg of titanium dioxide were stirred and mixed and the temperature was raised to 160 ° C and stirring was stopped to obtain a second premix; S3. Mix the first premix and the second premix, 2kg of dioctyl phthalate, 1kg of calcium-zinc composite stabilizer, 0.5kg of diisopropyl peroxide, 0.2kg of dispersant (a mixture of polyvinyl alcohol and hydroxypropyl methylcellulose in a mass ratio of 1:2), and 1kg of polyethylene wax, and add them to a twin-screw extruder. The temperature of the twin-screw extruder is: 180℃-185℃ in zone 1, 185℃-190℃ in zone 2, 170℃-180℃ in zone 3, 170℃-175℃ in zone 4, and 165℃-170℃ in zone 5. Melt extrude, cool, shape, and cut to obtain a composite reinforced PVC pipe. Example 2
[0025] The composite reinforcement materials include 8kg of modified carbon fiber and 4.5kg of modified nano-alumina.
[0026] The preparation steps of modified carbon fiber are as follows: A1. Soak 8kg of carbon fiber in 14L of acetone for 0.75h, wash and dry; A2. Soak the dried carbon fiber in 16L nitric acid solution for 1.25h, wash and dry; A3. Soak the dried carbon fiber in 12.5L coupling agent solution for 20 minutes, wash and dry to obtain modified carbon fiber.
[0027] The preparation steps of modified nano-alumina are as follows: 6.5 kg of 55-nanometer nano-alumina particles were added to an organic solvent, and 5 kg of aromatic amino acid was gradually added under stirring. The mixture was reacted at 120° C. for 7 h, and then washed and dried to obtain modified nano-alumina.
[0028] Preparation of a composite reinforced PVC pipe S1. Add 12.5kg of composite reinforcement material to 60kg of PVC resin and stir and mix until the temperature rises to 175°C and then stop stirring to obtain a first premix; S2. Stirring 60kg of PVC resin and 3kg of titanium dioxide and heating to 175°C and stopping stirring to obtain a second premix; S3. The first premix and the second premix, 3kg of dioctyl phthalate, 3kg of calcium-zinc composite stabilizer, 1.25kg of diisopropyl peroxide, 0.7kg of dispersant (a mixture of polyvinyl alcohol and hydroxypropyl methylcellulose in a mass ratio of 1:2), and 3kg of polyethylene wax are mixed and added into a twin-screw extruder. The temperature of the twin-screw extruder is: 180℃-185℃ in zone 1, 185℃-190℃ in zone 2, 170℃-180℃ in zone 3, 170℃-175℃ in zone 4, and 165℃-170℃ in zone 5. The premix is melt-extruded, cooled, shaped, and cut to obtain a composite reinforced PVC pipe. Example 3
[0029] The composite reinforcement materials include 10kg of modified carbon fiber and 5kg of modified nano-alumina.
[0030] The preparation steps of modified carbon fiber are as follows: A1. Soak 10kg of carbon fiber in 18L of acetone for 1h, wash and dry; A2. Soak the dried carbon fiber in 20L nitric acid solution for 2h, wash and dry; A3. Soak the dried carbon fiber in 16L coupling agent solution for 30 minutes, wash and dry to obtain modified carbon fiber.
[0031] The preparation steps of modified nano-alumina are as follows: 7 kg of 100-nanometer nano-alumina particles were added to an organic solvent, and 7 kg of aromatic amino acid was gradually added under stirring. The mixture was reacted at 140° C. for 3 h, and then washed and dried to obtain modified nano-alumina.
[0032] Preparation of a composite reinforced PVC pipe S1. Add 15kg of composite reinforcement material to 65kg of PVC resin and stir and mix until the temperature rises to 190°C and then stop stirring to obtain a first premix; S2. The 65kg PVC resin and 5kg titanium dioxide were stirred and mixed and the temperature was raised to 190 ° C and the stirring was stopped to obtain a second premix; S3. The first premix and the second premix, 4kg of dioctyl phthalate, 5kg of calcium-zinc composite stabilizer, 2kg of diisopropyl peroxide, 1.2kg of dispersant (a mixture of polyvinyl alcohol and hydroxypropyl methylcellulose in a mass ratio of 1:2), and 5kg of polyethylene wax are mixed and added into a twin-screw extruder. The temperature of the twin-screw extruder is: 180℃-185℃ in zone 1, 185℃-190℃ in zone 2, 170℃-180℃ in zone 3, 170℃-175℃ in zone 4, and 165℃-170℃ in zone 5. The premix is melt-extruded, cooled, shaped, and cut to obtain a composite reinforced PVC pipe.
[0033] Comparative Example 1 Compared with Example 2, this comparative example replaces the modified carbon fiber with ordinary carbon fiber.
[0034] Comparative Example 2 Compared with Example 2, this comparative example replaces the modified nano-alumina with ordinary nano-alumina.
[0035] The PVC pipe materials obtained in Examples 1-3 and Comparative Examples 1-2 were processed into test samples and the following performance tests were performed: Tensile properties: tested using a universal testing machine in accordance with GB / T1040-92 at a test temperature of 25°C; Bending performance: tested using a universal testing machine in accordance with GB / T9341-2000 at a test temperature of 25°C; Impact performance: According to GB / T 1843-2008, a 2mm notch was punched on the specimen for impact test; High-speed impact test: According to CJ / T 272-2008, the test temperature is 23℃.
[0036] The measured results are shown in the following table:
[0037] From the comparison results of the above-mentioned Examples 1 to 3 and Comparative Examples 1-2, it can be seen that the composite reinforced PVC pipe prepared in Example 2 is significantly better than Comparative Examples 1 and 2 in various mechanical performance indicators such as tensile strength, bending strength and impact strength. This shows that the method of the present invention, by introducing modified carbon fiber and modified nano-alumina, greatly improves the comprehensive mechanical properties of the prepared PVC pipe, especially in terms of tensile resistance, bending resistance and impact resistance. Compared with the traditional preparation method, the present invention not only effectively improves the overall strength and durability of the pipe, but also enhances the stability and applicability of the material, and broadens its potential market in applications requiring high strength and high durability.
[0038] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it should be understood by those skilled in the art that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the purpose and scope of the technical solutions of the present invention, which should be included in the scope of the claims of the present invention. The techniques, shapes, and structural parts not described in detail in the present invention are all known technologies.
Claims
1. A composite reinforced PVC pipe, characterized in that: The raw materials for its preparation include, by weight: 110-130 parts of PVC resin, 10-15 parts of composite reinforcement material, 1-5 parts of stabilizer, 1-5 parts of titanium dioxide, 2-4 parts of plasticizer, 1-5 parts of lubricant, 0.5-2 parts of crosslinking agent, and 0.2-1.2 parts of dispersant; The composite reinforcement material comprises 6-10 parts of modified carbon fiber and 4-5 parts of modified nano-alumina. The modified carbon fiber is obtained by first oxidation and then modification with a coupling agent. The modified nano-alumina is modified with aromatic amino acids.
2. A composite reinforced PVC pipe according to claim 1, characterized in that: The stabilizer is a calcium zinc composite stabilizer, the plasticizer is dioctyl phthalate, the lubricant is one or more of paraffin wax, polyethylene wax, and stearic acid amide, the crosslinking agent is dicumyl peroxide, and the dispersant is a mixture of polyvinyl alcohol and hydroxypropyl methylcellulose in a mass ratio of 1:
2.
3. A composite reinforced PVC pipe according to claim 1, characterized in that: The preparation steps of the modified carbon fiber include: A1. Soak the carbon fiber in the cleaning solvent for 0.5-1h, wash and dry; A2. Soak the dried carbon fiber in the oxidant solution for 0.5-2h, wash and dry; A3. Soak the dried carbon fiber in a coupling agent solution for 10-30 minutes, wash and dry to obtain the modified carbon fiber.
4. A composite reinforced PVC pipe according to claim 2, characterized in that: The cleaning solvent in step A1 is one of acetone and ethanol, the oxidant solution in step A2 is one of chloric acid and nitric acid, and the coupling agent solution in step A3 is silane or titanate.
5. The composite reinforced PVC pipe according to claim 1, characterized in that: The preparation steps of the modified nano-alumina include adding nano-alumina particles into an organic solvent, gradually adding aromatic amino acids in a stirring state, reacting at 100° C.-140° C. for 3-11 hours, washing and drying to obtain the modified nano-alumina.
6. A composite reinforced PVC pipe according to claim 5, characterized in that: The particle size of the nano-alumina is 10-100 nanometers.
7. The composite reinforced PVC pipe according to claim 5, characterized in that: The mass ratio of the nano-alumina to the aromatic amino acid is 1:(0.5-1).
8. The composite reinforced PVC pipe according to claim 5, characterized in that: The aromatic amino acids include tyrosine and phenylalanine.
9. The method for preparing a composite reinforced PVC pipe according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Add the composite reinforcement material to half of the PVC resin, stir and mix, and stop stirring when the temperature rises to 160-190°C to obtain a first premix; S2. Stir and mix the other half of the PVC resin and the titanium dioxide and heat to 160-190°C and stop stirring to obtain a second premix; S3. The first premix and the second premix as well as the plasticizer, stabilizer, crosslinking agent, dispersant and lubricant are mixed, added into a twin-screw extruder, melt-extruded, cooled, shaped and cut to obtain the composite reinforced PVC pipe.
10. The method for preparing a composite reinforced PVC pipe according to claim 9, characterized in that: The temperature of the twin-screw extruder is: 180°C-185°C in zone 1, 185°C-190°C in zone 2, 170°C-180°C in zone 3, 170°C-175°C in zone 4 and 165°C-170°C in zone 5.